1990
DOI: 10.1111/j.1399-302x.1990.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro method to study the adherence of bacteria to saliva‐treated tooth enamel sections

Abstract: An in vitro bacterial adherence assay which employed human tooth enamel sections precoated with saliva and an epifluorescent staining technique with acridine orange was developed. The assay was used to study the adherence properties of fresh and type strains of the following oral bacterial species: Bacteroides gingivalis, Bacteroides intermedius, Capnocytophaga species, Haemophilus aphrophilus, Actinobacillus actinomycetemcomitans, Peptostreptococcus species, Veillonella species, Actinomyces israelii, Streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
5
2
Order By: Relevance
“…We conclude that plasma proteins, with the ability to mediate adherence of bacteria associated with periodontal disease, might be major pellicle components, particularly close to the gingiva. Our findings support earlier suggestions (35) that binding to the pellicle is a mechanism by which periodontopathogens are retained on the tooth surface in close proximity to their natural habitat, the gingival crevice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We conclude that plasma proteins, with the ability to mediate adherence of bacteria associated with periodontal disease, might be major pellicle components, particularly close to the gingiva. Our findings support earlier suggestions (35) that binding to the pellicle is a mechanism by which periodontopathogens are retained on the tooth surface in close proximity to their natural habitat, the gingival crevice.…”
Section: Discussionsupporting
confidence: 92%
“…P. gingivalis is considered a late coloniser, which is established in dental plaque by the co‐aggregation with early colonising bacteria (23). The fact that it has been shown to bind to saliva components (35) as well as to pellicle‐bound plasma proteins (our own findings) may indicate that it also can bind to the dental pellicle. Considerable adherence of F. nucleatum to both saliva and plasma components is consistent with its frequent appearance in both the supra‐ and subgingival dental plaque (38).…”
Section: Discussionmentioning
confidence: 69%
“…An increase in A. actinomycetemcomitans adhesion to eukaryotic cells has been reported when HeLa cells pretreated with saliva are used (33). However, in the present study, pretreatment of the KB cells with pooled saliva had little or no effect on adhesion.…”
Section: Methodscontrasting
confidence: 54%
“…However, in the present study, pretreatment of the KB cells with pooled saliva had little or no effect on adhesion. The use of a single donor in the study by Sweet et al (33), rather than a pooled saliva sample used in our study, may explain this difference in adhesion. In (8).…”
Section: Methodscontrasting
confidence: 42%
“…It has been demonstrated that A.a. has a greater ability to adhere to saliva-coated human enamel than do nine other gram-negative or grampositive oral bacteria. 25 Adhesion of A.a. involves multiple determinants. The A.a. ATCC 43718 used in this study is a nonfimbriated strain.…”
Section: Discussionmentioning
confidence: 99%